ANALISIS STANDAR PELAYANAN PUBLIK KADANG CINTA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARANGANYAR - Ilmi, Kinanti Lanjaran; Sugiyarti, Sri Riris (Solidaritas, 2025)
The Population and Civil Registration Office of Karanganyar Regency issued the “Kadang Cinta” program for IKD activation services. This study aims to describe and analyze the “Kadang Cinta” public service standards at the Karanganyar Regency Population and Civil Registration Office. This type of research uses qualitative research with a descriptive approach. Data collection and conclusions using interviews, observation and documentation. This study uses the six dimensions of Ridwan and Sudrajat's theory (2009) which consists of: (1) Service Procedures, (2) Completion Time, (3) Service Fees, (4) Service Products, (5) Facilities and Infrastructure, and (6) Officer Competence. Based on the research results, it is shown with the following results: (1) The dimension of service procedures is not in accordance with service standards as seen from the ownership of requirements, the community is confused and has not realized the existence of IKD, (2) The dimension of completion time is not in accordance with service standards as seen from the server connection constraints that hamper the service process. (3) The dimension of service costs is in accordance with service standards as seen from the suitability of the fees set and there is transparency of costs so that there is no extortion, (4) The dimension of service products is in accordance with service standards as seen from the service products produced in accordance with the legal basis, provisions and those published, (5) The dimension of facilities and infrastructure is in accordance with service standards in Indonesia.